Pengaruh Kepemimpinan Kepala Sekolah, Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Guru di Yayasan Al Asyhar Tulakan Donorojo Jepara - Rohmat Rohmat; Slamet Utomo; Gunawan Setiadi (Peneliti.net, 2022)
The purpose of this study was to determine the effect of the principal's leadership on performance. To determine the influence of organizational culture on performance. To determine work motivation on performance. To analyze the influence of the principal's leadership on organizational culture. To analyze the influence of organizational culture on work motivation. To analyze the influence of the principal's leadership on work motivation. To analyze the influence of principal's leadership, organizational culture and motivation on teacher performance. This type of research is quantitative, which focuses on objective phenomena to be studied quantitatively. This research belongs to the type of expost facto research, namely research that aims to find out events that have occurred and then trace back to find out the factors that caused these events. The data analysis method used to see the influence between variables in this study is multiple linear regression analysis with the SPSS 23 program. The results showed that the principal's leadership had an effect on the performance of teachers at the Al Asyhar Tulakan Donorojo Foundation, Jepara. Organizational culture influences the performance of teachers at the Al Asyhar Tulakan Donorojo Foundation, Jepara. Work motivation affects the performance of teachers at the Al Asyhar Tulakan Donorojo Foundation, Jepara. The principal's leadership influences the organizational culture at the Al Asyhar Tulakan Donorojo Foundation, Jepara. Organizational culture influences work motivation at the Al Asyhar Tulakan Donorojo Foundation, Jepara. The principal's leadership influences work motivation at the Al Asyhar Tulakan Donorojo Foundation, Jepara. Principal leadership, organizational culture and motivation affect teacher performance at the Al Asyhar Tulakan Donorojo Foundation, Jepara.